2011
DOI: 10.1080/01490451.2010.489922
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Actvity and13C/12C Ratio as Evidence of N-Hexadecane and N-Hexadecanoic Acid Biodegradation in Agricultural and Forest Soils

Abstract: The dynamics of microbial degradation of exogenous contaminants, n-hexadecane and its primary microbial oxidized metabolite, n-hexadecanoic (palmitic) acid, was studied for topsoils, under agricultural management and beech forest on the basis the changes in O 2 uptake, CO 2 evolution and its associated microbial and non-microbial carbon isotopic signature, the respiratory quotient (RQ) and the priming effect (PE) of substrates. Soil microbial communities in agricultural soil responded to the n-hexadecane addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…However, PE became negligible in both experiments during 6-8 day exposure; it is possibly the mineralization time of aliphatic hydrocarbons or their partially oxidized products. The negative PE has been demonstrated previously in the processes of the microbial mineralization of n-hexadecanoic acid introduced into soil (Zyakun et al 2011). At the next period of the exposure, the PE values demonstrate the positive values of 300 % in experiment 1 and about 400 % in experiment 2.…”
Section: Priming Effect Of Oil Hydrocarbonsmentioning
confidence: 68%
See 2 more Smart Citations
“…However, PE became negligible in both experiments during 6-8 day exposure; it is possibly the mineralization time of aliphatic hydrocarbons or their partially oxidized products. The negative PE has been demonstrated previously in the processes of the microbial mineralization of n-hexadecanoic acid introduced into soil (Zyakun et al 2011). At the next period of the exposure, the PE values demonstrate the positive values of 300 % in experiment 1 and about 400 % in experiment 2.…”
Section: Priming Effect Of Oil Hydrocarbonsmentioning
confidence: 68%
“…Acceleration of SOM degradation (positive PE) was also observed in case of addition of an aliphatic hydrocarbon (n-hexadecane) to the soil. Introduction into soil of n-hexadecanoic acid, the product of n-hexadecane oxidation, resulted in the lower rate of SOM mineralization compared to native soil (negative PE) (Zyakun et al 2011). In the light of brief presentation of methods characterizing biodegradation and transformation of exogenous organic products entering the soil, the fate of crude oil in soils may be defined by the following parameters: (a) the rate of CO 2 production as result of mineralization of crude oil and SOM; (b) activation of mineralization of native soil organic matter by introduced substrate (priming effect); c) the ratio of the quantities of biomass of the microorganisms growing on oil hydrocarbons as a substrate and quantities of SOM mineralized into CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the unique metabolic system with extracellular enzymes the microbial community utilizes PHs for growth‐supporting carbon and energy, however they are toxic in high concentrations and thus the degradation of PHs requires adaptations and resource trade‐offs . The quantitative and qualitative transformation of PHs by microbial communities depends on the PHs characteristics (amount, nature, and age), environmental conditions (oxygen diffusion, temperature, physical and chemical PHs dispersion, nutrient availability) and composition of autochthonous microbial community .…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of PHs biodegradation intensity and microbial activity in soils can be determined by monitoring the PHs contamination and related metabolites; one of the most universal is CO 2 efflux as indicator of biologically processed carbon by respiration . It has been demonstrated that addition of exogenous organic substrate (e.g., glucose, cellulose, amino acids, etc.)…”
Section: Introductionmentioning
confidence: 99%